2013
DOI: 10.1128/mcb.00834-12
|View full text |Cite
|
Sign up to set email alerts
|

Yeast Protein Phosphatase 2A-Cdc55 Regulates the Transcriptional Response to Hyperosmolarity Stress by Regulating Msn2 and Msn4 Chromatin Recruitment

Abstract: We have identified Cdc55, a regulatory B subunit of protein phosphatase 2A (PP2A), as an essential activating factor for stress gene transcription in Saccharomyces cerevisiae. The presence of PP2A-Cdc55 is required for full activation of the environmental stress response mediated by the transcription factors Msn2 and Msn4. We show that PP2A-Cdc55 contributes to sustained nuclear accumulation of Msn2 and Msn4 during hyperosmolarity stress. PP2A-Cdc55 also enhances Msn2-dependent transactivation, required for ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 66 publications
2
36
1
Order By: Relevance
“…PKA excludes Msn2 from the nucleus by both inhibiting its nuclear import and by stimulating its nuclear export through phosphorylation of serine residues in the nuclear localization (NLS) and nuclear export (NES) sequences94344. We found that a fusion construct containing a heterologous NES and the Msn2 NLS (amino acids 576–704), which becomes dephosphorylated and concentrates into the nucleus upon glucose starvation43, neither responded to light nor H 2 O 2 (0.4 mM, Supplementary Fig.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…PKA excludes Msn2 from the nucleus by both inhibiting its nuclear import and by stimulating its nuclear export through phosphorylation of serine residues in the nuclear localization (NLS) and nuclear export (NES) sequences94344. We found that a fusion construct containing a heterologous NES and the Msn2 NLS (amino acids 576–704), which becomes dephosphorylated and concentrates into the nucleus upon glucose starvation43, neither responded to light nor H 2 O 2 (0.4 mM, Supplementary Fig.…”
Section: Resultsmentioning
confidence: 92%
“…Additional PKA-cognate Msn2 serine residues (S194, S451, S582 and S633 (ref. 44)) were also dephosphorylated in a Tsa1-dependent manner upon exposure to H 2 O 2 (Supplementary Fig. 3j and Supplementary Data 1 and 2).…”
Section: Resultsmentioning
confidence: 96%
“…Reportedly, alterations in TORC1 cues attenuate the transcriptional activity of Msn2/Msn4 via several factors, including PP2A phosphatase (17,36). Our study reveals that, despite the enhanced nuclear localization of Msn2 (and presumably Msn4) in response to acute oxidative stress, the expression of Msn2/Msn4-controlled genes is not significantly changed in oma1⌬ cells.…”
Section: Discussionmentioning
confidence: 67%
“…Despite the enhanced oxidative-stress-induced nuclear localization of Msn2, its function appears to be impeded in the oma1⌬ mutant. A recent report implicated protein phos- phatase 2A (PP2A) in facilitating Msn2/Msn4 association with chromatin via modulation of nuclear sequestration mechanisms in response to signals from TORC1 (17). Moreover, alterations in TORC1 cues can attenuate the transcriptional activity of Msn2/ Msn4 via several factors, including PP2A phosphatase (36).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation